Effectiveness of a programme comprising serial casting, botulinum toxin, splinting and motor training for contracture management: a randomized controlled trial. (June 2019) - Leung, Joan; King, Clayton; Fereday, Sarah
Objective: To determine the effectiveness of a programme comprising serial casting, botulinum toxin, splinting and motor training in contracture management. Design: A randomized trial with concealed allocation and assessor blinding, a deferred treatment cross-over design within the control group, was conducted. Setting: Inpatient Brain Injury Unit of a rehabilitation centre. Subjects: A total of 10 patients with severe acquired brain injury (13 ankles). Interventions: The intervention group received botulinum toxin and then serial casting. The control group was placed on a wait list for six weeks (control phase) and then received the same interventions as the intervention group (intervention phase). Both groups received splinting and motor training following serial casting. Main measures: The primary outcome was passive ankle dorsiflexion range. Secondary outcomes included spasticity, ankle dorsiflexor strength, Functional Independence Measure score for the walking item and walking speed. Results: The mean between-group difference for passive ankle dorsiflexion range at completion of casting was 26° (95% confidence interval (CI): 17–35); at Week 2, after casting was 24° (95% CI: 14–33). The mean within-group differences for passive ankle dorsiflexion at completion of casting, Week 2 after casting and Week 8 after casting were 26° (95% CI: 20–31), 26° (95% CI: 18–33) and 24° (95% CI: 19–30), respectively. These improvements were sustained at Week 2 and Week 8 after casting. Conclusions: A programme for contracture management comprising serial casting, botulinum toxin, motor training and splinting can be useful in improving joint range.